The Implementation of Demonstration Method to Increase Learning Outcome in Natural Science Lessons - Bambang Wiranto Pangaribuan; Natalina Purba; Kevin William Andri Siahaan; Eduard F Sidabutar; Veria Tika Sihombing; Diana Falentina Simamora; Johan R Matondang (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This research is motivated by the low understanding of students' concepts in science learning in grade 2 State Elementary Schools. Researchers provide solutions by applying the demonstration method, a learning method by demonstrating items, events, rules and sequences of carrying out an activity, either directly or through the use of teaching media that are relevant to the subject or material being presented. This type of research is classroom action research. This research has two cycles. Each cycle consists of two sessions and four phases, namely planning, implementation, observation and reflection. The subjects of this study were 2nd grade elementary school students, totaling 21 people. The results of the study concluded that the use of the demonstration method could improve student learning outcomes in science subjects in Grade 2 of State Elementary Schools.